Aperiodic crystals: thirty years since the discovery of quasicrystals - Landauro, Carlos V. (2011)
Almost thirty years after the discovery of quasicrystals and after the Nobel Prize in Chemistry awarded to their discoverer, this short paper reviews the quasicrystals from a particular point of view. In the present paper the state of the art knowledge of quasicrystals is presented starting from their discovery and finishing with their manipulation at the nanoscopic scale.